2021
DOI: 10.1093/cvr/cvab205
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Yap/Taz in cardiac fibroblasts attenuates adverse remodelling and improves cardiac function

Abstract: Aims Fibrosis is associated with all forms of adult cardiac diseases including myocardial infarction (MI). In response to MI, the heart undergoes ventricular remodeling that leads to fibrotic scar due to excessive deposition of extracellular matrix mostly produced by myofibroblasts. The structural and mechanical properties of the fibrotic scar are critical determinants of heart function. Yes-associated protein (Yap) and transcriptional coactivator with PDZ-binding motif (Taz) are the key effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 48 publications
3
55
0
Order By: Relevance
“…Elevated YAP and downregulated upstream Hippo kinase LATS1 were determined in the left ventricular tissue of HF patients, which was associated with cardiac fibroblast proliferation [42]. Recent studies also identified the activation of YAP and TAZ in resident cardiac fibroblasts from preclinical MI models (Figure 2) [18,19,27]. YAP and TAZ can directly induce the differentiation of fibroblasts into pathologic myofibroblasts [27,28].…”
Section: Hippo Signaling Pathway In Cardiac Fibrosismentioning
confidence: 97%
See 4 more Smart Citations
“…Elevated YAP and downregulated upstream Hippo kinase LATS1 were determined in the left ventricular tissue of HF patients, which was associated with cardiac fibroblast proliferation [42]. Recent studies also identified the activation of YAP and TAZ in resident cardiac fibroblasts from preclinical MI models (Figure 2) [18,19,27]. YAP and TAZ can directly induce the differentiation of fibroblasts into pathologic myofibroblasts [27,28].…”
Section: Hippo Signaling Pathway In Cardiac Fibrosismentioning
confidence: 97%
“…Understanding the mechanisms underlying fibrotic cardiac remodeling after injury remains a critical barrier to developing effective treatments for HF patients. An increasing number of studies have revealed important roles for Hippo signaling components in the development and progression of cardiac fibrosis [18][19][20]23,[27][28][29]35,37,39,[42][43][44][45][46][47][48]. While YAP/TAZ activation is crucial for driving cardiac fibrosis, their suppression was beneficial for preventing angiotensin II (AngII) or MI-induced fibrosis [18,19,29,44].…”
Section: Hippo Signaling Pathway In Cardiac Fibrosismentioning
confidence: 99%
See 3 more Smart Citations